Current and Next Generation Portable Screening Devices for Diabetic Retinopathy - Micheletti, J. Morgan (J Diabetes Sci Technol, 2016)
Diabetic retinopathy (DR) is the leading cause of legal blindness in the United States, and with the growing epidemic of diabetes, a global increase in the incidence of DR is inevitable, so it is of utmost importance to identify the most cost-effective tools for DR screening. Emerging technology may provide advancements to offset the burden of care, simplify the process, and provide financially responsible methods to safely and effectively optimize care for patients with diabetes mellitus (DM). We review here currently available technology, both in production and under development, for DR screening. Preliminary results of smartphone-based devices, “all-in-one” devices, and alternative technologies are encouraging, but are largely pending verification of utility when used by nonophthalmic personnel. Further research comparing these devices to current nonportable telemedicine strategies and clinical fundus examination is necessary to validate these techniques and to potentially overcome the poor compliance around the globe of current strategies for DR screening.